FAKTOR-FAKTOR YANG MEMENGARUHI PENGUNGKAPAN SUKARELA INTERNET FINANCIAL AND SUSTAINABILITY REPORTING - Yulius Kurnia Susanto; Yosafat Pujo Lukito (University of Merdeka Malang, 2013)
Internet Financial and Sustainability Reporting (IFSR) was voluntary disclosure. With no specific regulationson IFSR, some companies disclosed its informations about financial, sustainability, products, etc at companyswebsite independenly. Its website could interest investor, creditor, and internet user to know more about thecompany. The objective of this research was to test and analyze the factors that affected the voluntary disclosureby IFSR Index. Firm size, return on equity, leverage, liquidity, companys status, profitability, and outsideownership were the independent variables of this research. The samples of this research were 92 manufacturingcompanies listed at Indonesia Stock Exchange during 2008 till 2010 that had been selected by using purposivesampling method. The result of this research revealed that firm size and leverage influenced Internet Financialand Sustainability Reporting. Big companies had a good reporting information system and leaned to have theresources to produce more information.